Association between index-to-ring finger length ratio (2D:4D) in female with knee osteoarthritis - Mustapha, Mawardi (2017)
Introduction: Osteoarthritis (OA) is a major public health problem and the most common cause of disability. There are gender differences in the prevalence, incidence and severity of knee and hip OA, especially knee OA affecting more women than men. Digit ratio (2D:4D) is defined as the ratio of the length of index finger to length of ring finger. Lower digit ratio (2D:4D), is a proxy indicator of in-utero testosterone exposure, which was associated with aggression, risk taking behaviour as well as risk of total knee replacement for osteoarthritis. Objective: To determine the association of index-to-ring finger length ratio (2D:4D) in female with knee osteoarthritis and non-osteoarthritis (control) Methods: Comparative case control study was conducted, in which female patient with Osteoarthritis knees were compared with non-osteoarthritic female (control). Measurements will be taken from the tip of the respective finger to the basal crease. The length of the index finger (2D) will be divided by the length of the ring finger (4D) to obtain the 2D:4D ratio. The ratio was classified into 3 types. Type I (index longer than ring) common female pattern, type II (index=ring) intermediate pattern and type III (index shorter than ring) common male pattern. Results: A total of 136 female patients of OA and non OA each were selected in the study. In the OA, 48% (n = 66) were Type III 2D:4D ratio followed by Type I, 28% (n= 38) and Type II, 24% (n=32). Whereas, among non-osteoarthritis the highest 2D:4D ratio type was Type I which were 46%. With Pearson Chi Square Test, P-value obtained from the test was p < 0.001 which means there was statistically significant difference between 2D:4D ratio in female with knee OA and control.